Kode Etik Pengelolaan Limbah Bekas Dan Bahan Terkontaminasi Pada Laboratorium Kultur Jaringan Tanaman - Najwa Athifah Athifah; Ribi Zuhriah Sani Sani; Mhd Yusuf Nasution; Khairiza Lubis; Nurbaity Situmorang (Jurnal Biogenerasi, 2026)
This study aims to describe the management of used culture media waste and contaminated materials, and to assess the understanding of laboratory staff and interns regarding ethical principles in plant tissue culture laboratories. A descriptive qualitative method was applied using observation, questionnaires, and literature review. The results indicate that most respondents have a good understanding, reflected in their agreement on the importance of sterilization, waste segregation, use of personal protective equipment, and implementation of standard operating procedures (SOP). Respondents are also aware of the risks of laboratory waste to health and the environment. Ethical practices are recognized as part of professional responsibility, but require improvement through training, supervision, and consistent SOP implementation.